Margaret Kohlman letter to Oscar Allert regarding Peregrine Falcon sightings, May 29, 1939 - Kohlman, Margaretet al (1939)
Letter from Margaret Kohlman to Oscar Allert dated May 29, 1939. Kohlman details her sightings of a Peregrine Falcon that she originally misidentified as a Merlin. This letter was summarized in Allert's article "Notes on Certain Raptores in Allamakee, Clayton and Dubuque Counties, Iowa," published in Iowa Bird Life, vol. 9, no. 3. Epson - sheet feed/flatbed